A flexible transparent graphene/metal–organic framework complex hybrid chemical sensor for highly sensitive ethanol detection - Yong Hee Kim; Chang Ho Choi; Hyun Woo Song; Eun Kwang Lee; Dong‐Pyo Kim; Joon Hak Oh (EcoMat, 2024)
Abstract High‐performance flexible and transparent chemical sensors are key to achieving wearable electronics. Graphene with high transmittance and electrical properties is a suitable material for flexible and transparent chemical sensors. However, graphene has low detectivity to chemical substances. Here, we report hybrid chemical sensors fabricated by introducing a highly flat and smooth metal–organic framework (MOF) on graphene. The graphene chemical sensors functionalized with MOF on SiO2/Si wafer exhibit 22 times higher sensitivity of 6.07 μA ppm−1 in detecting ethanol than that of pristine graphene transistors of 0.28 μA ppm−1 and a low detection limit of 1 ppm. Furthermore, a flexible transparent 7 × 7 chemical sensor array exhibits great driving stability after the bending cycles of 105 at a bending radius of 1.0 mm and shows sensitivity of 0.11 μA ppm−1. Our findings demonstrate an efficient way to improve the chemical sensing ability of graphene for application in wearable chemical sensors.